2019
DOI: 10.20944/preprints201901.0277.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burnout and Engagement: Personality Profiles in Nursing Professionals

Abstract: The burnout syndrome, which affects so many healthcare workers, has recently awakened wide interest due to the severe repercussions related to its appearance. Even though job factors are determinant to its development, not all individuals exposed to the same work conditions show burnout, which demonstrates the importance of individual variables such as personality. The purpose of this study was to determine personality characteristics of a sample of nursing professionals based on the Big Five model, and then, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…This study also revealed that in both samples, gender, shift work, type of employment contract, the perception of work as stressful and the presence of leisure activities influenced the levels of workaholism, engagement and work–family interaction. Similar results have been identified, namely associated with the demanding physical and emotional professional performance, domestic chores and parental role, with women showing an increasingly active role at work, as well as the technological advancements that ensure constant professional connectedness leads to increased stress levels (Bakhamis et al., 2019; Bandeira et al., 2019; Molino et al., 2019; Pérez‐Fuentes et al, 2019; Zurlo et al., 2020).…”
Section: Discussionsupporting
confidence: 59%
“…This study also revealed that in both samples, gender, shift work, type of employment contract, the perception of work as stressful and the presence of leisure activities influenced the levels of workaholism, engagement and work–family interaction. Similar results have been identified, namely associated with the demanding physical and emotional professional performance, domestic chores and parental role, with women showing an increasingly active role at work, as well as the technological advancements that ensure constant professional connectedness leads to increased stress levels (Bakhamis et al., 2019; Bandeira et al., 2019; Molino et al., 2019; Pérez‐Fuentes et al, 2019; Zurlo et al., 2020).…”
Section: Discussionsupporting
confidence: 59%
“…Research over the past decades has shown that burnout has a host of negative consequences for individuals (e.g., Type 2 diabetes, coronary heart disease and severe injuries), organizations (e.g., absenteeism, poor performance and job dissatisfaction) and society at large (e.g., early mortality, hospitalization and disability pensions; for a review, see: [ 2 , 3 ]). Burnout has also been connected to the quality of care provided by healthcare professionals (e.g., nursing) [ 4 , 5 , 6 ]. Moreover, research has firmly established that burnout and its consequences exist in various occupations and environments [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12] Later, Maslach and Jackson (1981) defined burnout as a three-dimensional syndrome that consisted of depersonalization, emotional exhaustion, and low personal accomplishment. [345] Workload, lack of control, low income, injustice, and inability to understand society are recognized as important sources of burnout. [6] Burnout is especially common in jobs that are directly related to people, especially in the case of healthcare professionals who provide patient care services and face more challenges including communication with patients and their relatives as well as interaction with colleagues in teams.…”
Section: Introductionmentioning
confidence: 99%